Method for evaluating modification effect of modified powder

Through the sound insulation test of modified powder and unmodified powder, the problems of long detection cycle and high cost in the existing technology are solved, and the rapid and accurate evaluation of the powder modification effect is achieved, which is suitable for large-scale Monitoring requirements for production.

CN119147634AInactive Publication Date: 2024-12-17CHINA RESOURCES CEMENT TECH RES DEV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411597237.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing powder surface modification effect evaluation methods have problems such as long detection cycle, large material consumption and high cost, and it is difficult to meet the monitoring needs of large-scale production.

Method used

By mixing the modified powder with the unmodified powder with the resin and the curing agent, the sound insulation test was performed after curing, and the modification effect was evaluated by the sound insulation difference, which was simple to operate, low cost and short detection cycle.

Benefits of technology

The accurate evaluation of the surface modification effect of the modified powder is achieved, and the waste of finished materials is avoided. It is suitable for the preliminary testing needs of large-scale production. The test results are accurate and low-cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119147634A_ABST
    Figure CN119147634A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of powder evaluation methods, in particular to a modified powder modification effect evaluation method. The method for evaluating the modification effect of the modified powder comprises the following steps: mixing modified powder, resin and a curing agent, and curing to obtain a resin composite material A; mixing the unmodified powder, resin and a curing agent, and curing to obtain a resin composite material B; carrying out sound insulation index testing on the resin composite material A and the resin composite material B to obtain the sound insulation index of the resin composite material A and the sound insulation index of the resin composite material B; and evaluating the surface modification effect of the modified powder according to the difference between the sound insulation index of the resin composite material A and the sound insulation index of the resin composite material B. The method is simple to operate, low in test cost and short in test period, avoids material consumption caused by evaluation by using a finished product result, and can meet the requirement on detection before the modified powder is used in large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of powder evaluation methods, and in particular to a method for evaluating the modification effect of modified powders. Background Art

[0002] The modification of powder fillers is mainly achieved by chemical modifiers adsorbing, coating, and chemical reactions on the surface of powder fillers. For example, quartz powder involves a variety of effects in the process of ball milling modification, such as physical effects, chemical effects, and mechanochemical effects. It can not only change the morphology, particle size, and structure of inorganic particles, such as particle refinement, grain refinement, cracks, density changes (apparent density, true density), and specific surface area, but also give the particle surface higher active points, which will release exo-excited electrons and activate polymers to participate in the reaction. Quartz sand will not only break solid materials under the action of high-energy ball milling mechanical force, but also cause lattice defects, increase the internal energy of solid materials, and cause Si-O bonds to break, and produce higher active points on the surface, making it in an unstable chemically active state, which is easy for active monomers to react.

[0003] At present, there are two main methods for evaluating the effect of powder surface modification. One method is the application result evaluation method: the effect of the surface modification is evaluated based on the mechanical properties and comprehensive properties of the finished product to which the modified powder filler is added. This application result evaluation method is currently a commonly used method in the industry. Although the results are accurate and reliable, this detection method consumes finished product materials and has a long detection cycle. It is a post-event result feedback and cannot meet the needs of monitoring the powder filler before use in mass production. The other is the pre-evaluation method: the surface characteristics of the modified powder filler are measured to evaluate the effect of the surface modification. This test method is very complicated, time-consuming and labor-intensive, the test instrument is expensive, and the test cost is very high, which is not conducive to widespread use.

[0004] In view of this, this invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a method for evaluating the modification effect of modified powders, which has the advantages of simple operation, low test cost and short test cycle, avoiding the material consumption caused by the evaluation of finished product results, and can be applicable to the need for pre-use detection of modified powders in large-scale production.

[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: The present invention provides a method for evaluating the modification effect of modified powder, comprising the following steps: The modified powder, resin and curing agent are mixed and cured to obtain a resin composite material A; the unmodified powder, resin and curing agent are mixed and cured to obtain a resin composite material B; the resin composite materials A and B are subjected to sound insulation tests to obtain the sound insulation of the resin composite materials A and the sound insulation of the resin composite materials B; the surface modification effect of the modified powder is evaluated according to the difference between the sound insulation of the resin composite materials A and the sound insulation of the resin composite materials B.

[0007] Further, the powder includes powder containing silicon dioxide; And / or, the particle size of the powder is 200-5000 mesh.

[0008] Furthermore, the powder containing silicon dioxide includes quartz powder and glass powder.

[0009] Furthermore, the invention comprises at least one of the following features (1) to (3): (1) A method for preparing the modified powder, comprising: modifying the powder with a modifier to obtain the modified powder; (2) The modifier includes at least one of a silane coupling agent, a titanate ester and a phosphate ester; (3) The modification includes: mixing the modifier and the powder at 80-100° C. for 3-5 minutes and then drying.

[0010] Furthermore, the silane coupling agent includes at least one of KH550, KH560 and KH570.

[0011] Furthermore, the resin includes unsaturated polyester resin.

[0012] Furthermore, the curing agent includes peroxide.

[0013] Furthermore, the ratio of the mass of the modified powder or the unmodified powder to the mass of the resin is (3-10):20.

[0014] Furthermore, the mass of the curing agent is 0.5% to 1% of the mass of the resin.

[0015] Furthermore, the curing includes: curing at 60-80° C. for 2-4 hours.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention mixes the modified powder and the unmodified powder with resin respectively, solidifies them, and then performs a sound insulation test to obtain the sound insulation; the difference in sound insulation between the unmodified powder and the modified powder is accurately measured, so as to accurately evaluate the modification effect of the modified powder; the modified powder modification effect evaluation method of the present invention is simple to operate, has low test cost, and short detection cycle, avoids the problem of material consumption caused by using finished product results for evaluation, and can be applicable to the need for pre-use detection of modified powders in large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 It is a schematic diagram of the sound insulation test of the present invention. DETAILED DESCRIPTION

[0019] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0020] The following is a specific description of a method for evaluating the modified powder modification effect of the present invention.

[0021] In some embodiments of the present invention, a method for evaluating the modified powder modification effect is provided, comprising the following steps: The modified powder, resin and curing agent are mixed and cured to obtain resin composite material A; the unmodified powder, resin and curing agent are mixed and cured to obtain resin composite material B; the resin composite materials A and B are subjected to sound insulation tests to obtain the sound insulation of the resin composite materials A and the sound insulation of the resin composite materials B; according to the difference in the sound insulation of the resin composite materials A and the sound insulation of the resin composite materials B, the modified ones are evaluated and compared with different sound insulation values.

[0022] The surface of different modified powders has different properties. Different surface properties will greatly affect the compatibility and mixing uniformity with the resin in the later stage. The dispersion of powders in the resin system has a great influence on the overall sound propagation of the system. The different dispersion of powders in the resin leads to different sound insulation effects. By comparing different sound insulation values, we can obtain different surface modification effects of modified powders.

[0023] Different modified powders have different dispersibility in the resin, which leads to differences in sound propagation. It is more convenient and simple to evaluate the modification effect of the powder based on the existence of this difference. The higher the sound insulation, the better the powder is dispersed in the resin. The dispersion of powders with different surface modifications in the resin can be accurately obtained.

[0024] The present invention mixes the modified powder and the unmodified powder with resin respectively, solidifies them, and then performs a sound insulation test to obtain the sound insulation; the difference in sound insulation between the unmodified powder and the modified powder is accurately measured, so as to accurately evaluate the effect of the modified powder; according to the sound insulation values ​​of the resin composite material containing the unmodified powder and the resin composite material containing the modified powder, the better the powder is dispersed in the resin, the higher the sound insulation; by comparing the sound insulation values ​​of the resin composite material containing the modified powder and the resin composite material containing the unmodified powder, the greater the difference between the two, the higher the sound insulation of the resin composite material of the modified powder, the better the dispersibility of the modified powder in the resin, and the better the modification effect.

[0025] The modified powder modification effect evaluation method of the present invention is simple to operate, has low testing cost and short testing cycle, avoids the problems of material consumption caused by using finished product results for evaluation, and can be applicable to the need for pre-use testing of modified powders in large-scale production.

[0026] The test results of the modified powder modification effect evaluation method of the present invention are less affected by manual operation and human endpoint judgment, have high resolution, and can meet the needs of evaluating the effect of powder surface modification during mass production; compared with the oil absorption value using the ball rubbing method, human errors have a greater impact on the results; the test results of the sound insulation test are less affected by manual operation, and the test results are more accurate.

[0027] The method of evaluating the modification effect of powder by comparing the change of contact angle is very complicated, time-consuming and labor-intensive, the testing instrument is expensive, and the testing cost is very high; compared with the above method, the modified powder modification effect evaluation method of the present invention has simple testing steps, low testing instrument price, low testing cost, and is conducive to wide use.

[0028] The modified powder modification effect evaluation method of the present invention has a short detection time and a simple process, which is conducive to the demand for large-scale powder detection before use.

[0029] In the modified powder modification effect evaluation method of the present invention, the sound insulation test: refer to the standard method GB / T31004.1-2014 Acoustic buildings and building components sound insulation sound intensity method measurement Part 1: Laboratory measurement; the schematic diagram of the sound insulation test is as follows Figure 1 As shown; the test was carried out using an acoustic impedance tube.

[0030] In some embodiments of the present invention, the powder includes a powder containing silicon dioxide.

[0031] In some embodiments of the present invention, the particle size of the powder is 200-5000 mesh; typically but not limiting, for example, the particle size of the powder can be 200 mesh, 500 mesh, 1000 mesh, 2000 mesh, 3000 mesh, 4000 mesh, 5000 mesh or a range of any two thereof.

[0032] In some specific embodiments of the present invention, the powder containing silicon dioxide includes quartz powder and glass powder; preferably, the powder containing silicon dioxide includes quartz powder.

[0033] In some embodiments of the present invention, a method for preparing a modified powder includes: modifying a powder (unmodified powder) using a modifier to obtain a modified powder.

[0034] In some embodiments of the present invention, the modifier includes at least one of a silane coupling agent, a titanate, and a phosphate.

[0035] In some embodiments of the present invention, the modification includes dry modification, which specifically includes the following steps: mixing the modifier and the powder at 80-100° C. for 3-5 minutes, and then drying.

[0036] In some specific embodiments of the present invention, the silane coupling agent includes at least one of KH550, KH560 and KH570.

[0037] The preparation method of quartz powder for organic quartz stone slabs is to grind quartz raw materials through a ball mill. As the particle size of quartz powder continues to decrease, the specific surface area increases, the surface energy increases, and it is easy to agglomerate together. It has poor affinity with polymer materials, and when used as a filler, it is unevenly dispersed and easily agglomerated, which increases the resin content, and causes local deviations in the quartz powder and resin content, affecting the comprehensive performance of the final material. Therefore, it is necessary to modify the surface of quartz powder when preparing organic-inorganic composite materials.

[0038] The quartz powder was modified with silane coupling agents KH550, KH560 and KH570 respectively. The organic functional groups in the three silane coupling agents have different structural properties. KH550 is an amino silane, and the amino group is a polar group with strong hydrophilicity, so the modified powder is hydrophilic; KH570 is a methacryloxy silane, which is a non-polar group, and the modified powder has good hydrophobicity; and KH560 is an epoxy silane, and the epoxy group is a group between hydrophobic and hydrophilic. The hydrophobicity of the powder modified with KH560 is between the above two. The surface of the powder modified by different coupling agents has different properties. Different surface properties will greatly differ in the compatibility and mixing uniformity with the resin in the later stage.

[0039] In some embodiments of the present invention, the quartz powder is modified by using a silane coupling agent, comprising the following steps: The quartz powder and the silane coupling agent are mixed with high-speed stirring at 80-100° C. for 3-5 minutes, and then dried to obtain modified quartz powder.

[0040] In some embodiments of the present invention, the resin includes but is not limited to unsaturated polyester resin; preferably, the resin includes ortho-phthalic unsaturated resin or para-phthalic unsaturated resin.

[0041] In some embodiments of the present invention, the curing agent includes but is not limited to peroxide; preferably, the curing agent includes but is not limited to methyl ethyl ketone peroxide and / or dibenzoyl peroxide.

[0042] In some embodiments of the present invention, the ratio of the mass of the modified powder or the unmodified powder to the mass of the resin is (3~10):20; typically but not limitatively, for example, the ratio of the mass of the modified powder or the unmodified powder to the mass of the resin can be 3:20, 4:20, 5:20, 6:20, 7:20, 8:20, 9:20, 10:20 or a range of any two thereof.

[0043] In some embodiments of the present invention, the mass of the curing agent is 0.5% to 1% of the mass of the resin; typically but not limiting, for example, the mass of the curing agent is 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% of the mass of the resin or a range consisting of any two thereof.

[0044] In the modified powder modification effect evaluation method of the present invention, the amount of modified powder, resin and curing agent used is the same as that of unmodified powder, resin and curing agent; that is, the sound insulation of modified powder with different surface properties and unmodified powder at the same resin dosage is compared.

[0045] In some embodiments of the present invention, curing includes: curing at 60-80°C for 2-4 hours; typically but not limiting, for example, the curing temperature can be 60°C, 65°C, 70°C, 75°C, 80°C or a range consisting of any two thereof; the curing time can be 2h, 3h, 4h or a range consisting of any two thereof.

[0046] The present invention mixes the modified powder and the unmodified powder with a resin and a curing agent respectively, and then puts the mixture into a mold for vacuuming and curing, and then performs a sound insulation test to obtain the sound insulation values ​​of different powders.

[0047] 50g of ortho-phthalic unsaturated polyester resin, 200g of unmodified quartz powder with a particle size of 325 meshes and 0.25g of methyl ethyl ketone peroxide are stirred and mixed, put into a mold (mold size: a cylinder with a diameter of 10cm and a thickness of 0.5cm) for vacuuming, and cured at 60-80°C for 2h to obtain a resin composite material; the resin composite material is subjected to a sound insulation test to obtain the sound insulation of the resin composite material containing unmodified quartz powder.

[0048] Unmodified quartz powder with a particle size of 325 mesh and silane coupling agent KH550 are mixed with high-speed stirring at 80-100° C. for 3-5 minutes and then dried to obtain quartz powder modified with silane coupling agent KH550.

[0049] Unmodified quartz powder with a particle size of 325 mesh and silane coupling agent KH560 are mixed with high-speed stirring at 80-100° C. for 3-5 minutes and then dried to obtain quartz powder modified with silane coupling agent KH560.

[0050] Unmodified quartz powder with a particle size of 325 mesh and silane coupling agent KH570 are mixed with high-speed stirring at 80-100° C. for 3-5 minutes and then dried to obtain quartz powder modified with silane coupling agent KH570.

[0051] Sound insulation test: refer to the standard method GB / T31004.1-2014 Acoustic buildings and building components sound insulation measurement by sound intensity method Part 1: Laboratory measurement.

[0052] Example 1 The modified powder modification effect evaluation method provided in this embodiment comprises the following steps: 50g of ortho-phthalic unsaturated polyester resin, 200g of quartz powder modified by silane coupling agent KH550 with a particle size of 325 mesh, and 0.25g of methyl ethyl ketone peroxide were stirred and mixed, put into a mold (mold size: a cylinder with a diameter of 10cm and a thickness of 0.5cm) for vacuuming, and cured at 60-80°C for 2h to obtain a resin composite material; the resin composite material was subjected to a sound insulation test to obtain the sound insulation of the resin composite material.

[0053] Example 2 The modified powder modification effect evaluation method provided in this embodiment comprises the following steps: 50g of ortho-phthalic unsaturated polyester resin, 200g of quartz powder modified by silane coupling agent KH560 with a particle size of 325 mesh, and 0.25g of methyl ethyl ketone peroxide were stirred and mixed, put into a mold (mold size: a cylinder with a diameter of 10cm and a thickness of 0.5cm) for vacuuming, and cured at 60-80°C for 2h to obtain a resin composite material; the resin composite material was subjected to a sound insulation test to obtain the sound insulation of the resin composite material.

[0054] Example 3 The modified powder modification effect evaluation method provided in this embodiment comprises the following steps: 50g of ortho-phthalic unsaturated polyester resin, 200g of quartz powder modified by silane coupling agent KH560 with a particle size of 325 mesh, and 0.25g of methyl ethyl ketone peroxide were stirred and mixed, put into a mold (mold size: a cylinder with a diameter of 10cm and a thickness of 0.5cm) for vacuuming, and cured at 60-80°C for 2h to obtain a resin composite material; the resin composite material was subjected to a sound insulation test to obtain the sound insulation of the resin composite material.

[0055] The test results of the sound insulation of the resin composite materials of Examples 1 to 3 and the test results of the sound insulation of the resin composite material containing unmodified quartz powder (unmodified quartz powder) are shown in Table 1.

[0056] The oil absorption values ​​of quartz powder modified by silane coupling agent KH550, quartz powder modified by silane coupling agent KH560, quartz powder modified by silane coupling agent KH570 and unmodified quartz powder were tested, and the results are shown in Table 1.

[0057] The test method for oil absorption value is: refer to the test method for oil absorption value in the standard method GB / T 19281-2014 "Calcium Carbonate Analysis Method".

[0058] Table 1

[0059] As can be seen from Table 1, the present invention compares the slurries of modified quartz powder and unmodified quartz powder with different surface properties at the same resin dosage. The unmodified quartz powder has obvious agglomeration phenomenon and the morphology between particles is also uneven. This agglomeration phenomenon leads to uneven distribution in the resin slurry, resulting in poor performance of the resin composite material in terms of sound insulation performance. After modification with a silane coupling agent, the dispersibility and stability of the quartz powder are significantly improved, and it presents a more uniform distribution state in the resin slurry. The appearance of the resin composite material is uniform, and the sound insulation is improved.

[0060] The accuracy of the sound insulation test method is verified by the oil absorption value test. The oil absorption value decreases with the improvement of the powder dispersibility, which can prove that the modified powder has better dispersibility in the resin. The higher the sound insulation value, the better the powder is dispersed in the resin. The modified powder modification effect evaluation method of the present invention can accurately obtain the dispersion of powders with different surface treatments in the resin, accurately measure the difference in sound insulation between unmodified powder and modified powder, and accurately evaluate the effect of the modified powder.

[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for evaluating the modification effect of modified powder, characterized in that: The steps include: The modified powder, resin and curing agent are mixed and cured to obtain a resin composite material A; the unmodified powder, resin and curing agent are mixed and cured to obtain a resin composite material B; the resin composite materials A and B are subjected to sound insulation tests to obtain the sound insulation of the resin composite materials A and the sound insulation of the resin composite materials B; the surface modification effect of the modified powder is evaluated according to the difference between the sound insulation of the resin composite materials A and the sound insulation of the resin composite materials B.

2. The modified powder modification effect evaluation method according to claim 1, characterized in that: The powder includes a powder containing silicon dioxide; And / or, the particle size of the powder is 200-5000 mesh.

3. The modified powder modification effect evaluation method according to claim 2, characterized in that: The powder containing silicon dioxide includes quartz powder and glass powder.

4. The modified powder modification effect evaluation method according to claim 2, characterized in that: The invention comprises at least one of the following features (1) to (3): (1) A method for preparing the modified powder, comprising: modifying the powder with a modifier to obtain the modified powder; (2) The modifier includes at least one of a silane coupling agent, a titanate ester and a phosphate ester; (3) The modification includes: mixing the modifier and the powder at 80-100° C. for 3-5 minutes and then drying.

5. The modified powder modification effect evaluation method according to claim 4, characterized in that: The silane coupling agent includes at least one of KH550, KH560 and KH570.

6. The modified powder modification effect evaluation method according to claim 1, characterized in that: The resin includes an unsaturated polyester resin.

7. The modified powder modification effect evaluation method according to claim 1, characterized in that: The curing agent includes a peroxide.

8. The modified powder modification effect evaluation method according to claim 1, characterized in that: The ratio of the mass of the modified powder or the unmodified powder to the mass of the resin is (3-10):

20.

9. The modified powder modification effect evaluation method according to claim 1, characterized in that: The mass of the curing agent is 0.5% to 1% of the mass of the resin.

10. The modified powder modification effect evaluation method according to claim 1, characterized in that: The curing comprises: curing at 60-80° C. for 2-4 hours.

Citation Information

Patent Citations

  • Method for measuring surface activation degree of modified powder material

    CN103454180A

  • Toughened epoxy resin sound insulation material and preparation method thereof

    CN112920554A

  • Method for evaluating modification effect of hydrophobic surface modified powder

    CN115201419A

  • Method for modifying powder particle surface

    JP2018104392A